Drivers of post-adoption of e-wallet among academics in Palestine: An extension of the expectation confirmation model - Daragmeh, Ahmad; Saleem, Adil; Bárczi, Judit; Sági, Judit (Frontiers in Psychology, 2022)
E-Wallet is one of the recent innovations in the field of payments. However, despite numerous studies on the adoption of e-financial systems, the post-adoption phase is largely neglected. In this paper, we use the extended Expectation Confirmation Model (ECM) to address this gap by focus-ing on investigating consumers' continuous intentions regarding the use of an e-Wallet service. We conducted an electronic questionnaire-based survey among 503 e-Wallet users in Palestine. Using structural equation modeling to analyze the conceptual model of the study, our results confirm that satisfaction, trust, and perceived usefulness have a significant impact on consumers' continuous intention towards e-Wallet. In addition, the study found that perceived security has an in-significant influence on consumer satisfaction. The study has several implications: E-Wallet providers are advised to improve their services in terms of performance, privacy and security to en-sure customer loyalty in this competitive industry.